1975
DOI: 10.1080/00207597508247325
|View full text |Cite
|
Sign up to set email alerts
|

Description of White and Black Faces by White and Black Subjects

Abstract: A previous experiment by Shepherd, Deregowski and Ellis (1974) showed that white subjects are better at remembering white faces than black faces, and that black subjects are superior at recognizing black compared with white faces. The present experiment was designed to investigate the frequencies with which white and black subjects use different facial features when describing faces. It was found that black and white subjects did differ in their descriptions of faces, which was interpreted as reflecting differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
83
0
1

Year Published

1979
1979
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(89 citation statements)
references
References 6 publications
5
83
0
1
Order By: Relevance
“…(Additional data, not shown here or in the original report, corroborate the accuracy of both measures , but see Footnote I). In spite of its high level of variability, the mouth appears to be relatively unimportant for identification according to some stud ies (Davies et al, 1977;Ellis, Deregowski, & Shepherd, 1975 ;Fisher & Cox , 1975 ;Goldstein & Mackenberg, 1966), but other investigators report contrary findings (Lin, 1964;Seamon, Stolz, Bass, & Chatinover, 1978) .…”
Section: Saliency Of Feature Variability To Face Recognitionmentioning
confidence: 78%
See 2 more Smart Citations
“…(Additional data, not shown here or in the original report, corroborate the accuracy of both measures , but see Footnote I). In spite of its high level of variability, the mouth appears to be relatively unimportant for identification according to some stud ies (Davies et al, 1977;Ellis, Deregowski, & Shepherd, 1975 ;Fisher & Cox , 1975 ;Goldstein & Mackenberg, 1966), but other investigators report contrary findings (Lin, 1964;Seamon, Stolz, Bass, & Chatinover, 1978) .…”
Section: Saliency Of Feature Variability To Face Recognitionmentioning
confidence: 78%
“…Even though the nose seems to be one of the most variable features of the face, it does not appear to be important in facial identification (Ellis, Shepherd, & Davies, 1975 ;Goldstein & Mackenberg, 1966;Lin, 1964; see Davies, Ellis, & Shepherd, 1977, for short review of pertinent literature). On the other hand, Ellis, Deregowski, and Shepherd (1975) report that when describing faces, the nose is mentioned as frequently as lips and eyebrows, a finding that suggests that some features may be salient for one cognitive process but not for another. Most of the research just cited studied full-face stimuli, and in those studies the nose may have lost its potency as a cue for identification because it is a three-dimensional feature best viewed in profile.…”
Section: Saliency Of Feature Variability To Face Recognitionmentioning
confidence: 95%
See 1 more Smart Citation
“…Black African and White European faces have different physiognomic variability for different features (McClelland & Chappell, 1998): Black faces have more variability in the nose and mouth shape than the eye and hair colour, whereas White faces have the reverse pattern. Ellis, Deregowski, & Shepherd (1975) have shown that Black and White participants tend to describe faces based on these differences: White participants described the eye and hair colour more frequently than the nose and mouth shape, whereas Black participants showed the reverse pattern. Based on this evidence, Hills and Lewis (2006) used a perceptual learning paradigm to train White participants to encode the features that distinguish between Black faces (i.e., the nose and mouth) and managed to reverse the ORB and actually make their participants recognise Black faces more accurately than White faces.…”
mentioning
confidence: 99%
“…Numerous studies have indicated that hair is a primary distinctive feature in the perception and categorization of faces (Brown & Perrett, 1993;Ellis, Deregowski, & Shepherd, 1975;Haig, 1986;Roberts & Bruce, 1988;Wright & Sladden, 2003). Studies examining the face's internal features, however, have indicated that the eyes/eyebrow region are often the most salient cues in perceiving and recognizing faces, followed by the mouth/lips region (Brown & Perrett, 1993;Davies, Ellis, & Shepherd, 1977;Haig, 1986;Shepherd, Davies, & Ellis, 1981).…”
mentioning
confidence: 99%